Kompetencje dziennikarzy politycznych w programie typu talk-show – meritum, forma, retoryka (na przykładzie programu Studio Polska) - Grzegorzewski, Krzysztof (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The article focuses on the qualitative content analysis of a talk-show called Studio Polska, broadcast by the Polish national news channel TVP Info. The author researches the content of the programme, its form, as well as the verbal behaviour of journalists and programme participants, using selected rhetorical methods of textual analysis. The purpose is to evaluate the quality of the programme as well as the competence of journalists who host it.
Competences of political journalists in a talk show: essence, form, and rhetoric (on the example of the Studio Polska talk-show)
Keywords: rhetoric; eristic; TV; manipulation; propaganda; talk-show